Formulation of a Corporate Political Strategy in an Emerging Market : Subsidiaries of Finnish MNEs in Vietnam - Lahti, Jukka (My University, 2019)
Emerging markets have become an attractive business destination for multinational enterprises (MNEs) seeking new business opportunities beyond the developed and well-established markets. Even though emerging markets offer growth and new business opportunities, the companies are also exposed to complex political and legal environment in their host countries. Companies may seek to answer these challenges by formulating a corporate political strategy (CPS). After conducting multiple economic reforms that broke existing trade and investment barriers, Vietnam has become an attractive destination for foreign MNEs. The GDP and the wealth of the middle-class in Vietnam have increased significantly in recent years, as Vietnam has opened up for foreign investment and trade. Finnish MNEs have been amongst the ones investing in Vietnam for a quite some time, but there still exists a great potential for future growth and expansion. This study aims to fill a visible research gap in a rather unstudied area of academic research by investigating how the political strategy of the subsidiaries of Finnish MNEs in Vietnam is formulated. The main research question is studied through three sub-objectives, which include the following aspects of CPS formulation: approach, level of participation and strategy. The empirical results showed that Finnish MNEs had employed both relational and transactional approach to corporate political activity (CPA). The companies also participated simultaneously both individually and collectively in CPA. They used mainly tactics included in the information strategy, with specific emphasis on different forms of lobbying. The empirical data was collected by conducting qualitative theme interviews with executives from three different subsidiaries of Finnish MNEs operating in Vietnam. For further research, the study recommends similar research to be conducted on a more comprehensive group of MNEs from different countries. In addition, it is recommended that different mediating effects regarding, e.g. the influence of managers’ backgrounds and host companies are studied further, along with the effect of different political strategies in a company’s success.
Keywords: emerging markets, corporate political strategy, Vietnam